A Contrastive Study on Korean and Cia-Cia Language Vowels Based on an Acoustic Experiment - Achmad Rio Dessiar (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
The Cia-Cia language, which is spoken by around 79.000 people in the Bau-Bau area of Buton Island, does not have its own writing system. In 2009, the Korean alphabet, Hangeul, was approved by the Bau-Bau city government for transcribing Cia-Cia, owing to the similarity of phonemes in Korean to those in Cia-Cia. This research aimed to compare the acoustics of monophthongs in the Korean and Cia-Cia languages with an experimental phonetic approach and to discuss writing system problems in Cia-Cia when adopting the Korean writing system. Based on the classification, the Cia-Cia vowels /i, e, a, u, and o/ are equivalent to the Korean vowels /이 ([i]), 에 ([e]), 아 ([a]), 우 ([u]), 오 ([o])/. However, there are two Korean vowels that have no Cia-Cia equivalents namely, /으/ ([ɨ]) and /어/ ([ə]). In general, the vowel equivalents between the two languages have significant differences in terms of their acoustic characteristics. Nonetheless, unlike other vowel equivalents, the Cia-Cia vowel /u/ and Korean vowel /우/ ([u]) when pronounced show similar phonetic features in terms of position and oral cavity opening level. In contrast, the Cia-Cia vowel /a/ and Korean vowel /아/ ([a]) when pronounced is shown to have the same oral cavity opening level, but different tongue positions. The use of the vowel /으/ ([ɨ]) in Hangeul's writing in transcribing particular Cia-Cia words is a unique feature of Korean grammar. This renders some transcriptions different from the pronunciation of the source Cia-Cia word. This is because of the limitations of Korean syllables, which, unlike Cia-Cia words, are not able to be written as double consonants.